A SOCIAL DIVISION OF RESPONSIBILITY FOR HEALTH - Kniess, Johannes (Les ateliers de l'éthique / The Ethics Forum, 2018)
When is it fair that some people are less healthy than others due to their own individual choices and preferences? In this paper, I explore two alternative answers. The first is a luck-egalitarian account that holds people responsible for choices that society could have reasonably expected them to avoid. I argue that this account is indeterminate and go on to sketch an alternative proposal based on Rawls’s idea of a “social division of responsibility.” This latter approach connects the notion of responsibility for health to the social conditions under which health-related behaviour is developed.